The Effect of BI Rate, USD to IDR Exchange Rates, and Gold Price on Stock Returns Listed in the SRI KEHATI Index - Utama, Oktavian Yodha; Puryandani, Siti (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study aims to determine the effect of BI rate, USD to IDR exchange rates, and gold price on stock returns listed in the SRI KEHATI Index for the period January to December 2018. The population in this research is companies listed on the Indonesia Stock Exchange. The sample is determined by using a purposive sampling method. Some criteria of the sample are companies that: had entered to the SRI KEHATI index respectively from January to December 2018, reported the 2018 monthly financial report, were not suspended by the IDX during the study period, so that obtained a sample of 23 companies with total data is 268. This study used quantitative data analysis in the form of time-series data from January to December 2018. The data collection method used in this study is the documentation method. The analytical tool in this study is the multiple regression analysis. In this study, data is processed by using the SPSS program 21. The results show that the BI rate has a significant positive effect on stock returns, the USD to IDR exchange rate has a significant negative effect on stock returns, and gold price does not have a significant effect on stock returns.